Interregionale Arbeitskräftewanderungen: theoretische Erklärungsansätze und empirischer Befund - Eckhardt Bode; Sebastian Zwing (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The paper surveys the recent theoretical and empirical literature on the economic determinants of interregional labor migration. In the first part, theoretical approaches are outlined, in the second part, results of several empirical investigations are surveyed. The authors conclude that regional wage differences do, indeed, induce interregional labor migration, as theoretical approaches suggest. However, the impact of wages on migration seems to be limited. More important are regional differences in employment opportunities. Regions with comparatively low unemployment rates, resp. high employment probabilities, tend to exhibit net in-migration, whereas regions with higher unemployment rates tend to exhibit net out-migration. Other important factors influencing migration decisions are - at least at the microeconomic level - the migrant's age and qualification. At the macro level, however, these determinants often are insignificant. The same holds for several region-specific determinants such as urbanization, climate, or social benefits.
Keywords: J24; J61; R23; 330; Regionale Arbeitsmobilität; Regionale Lohnstruktur; Regionale Arbeitslosigkeit; Theorie; Welt